Prediksi Pergerakan Harga Valas Menggunakan Algoritma Neural Network - Castaka Agus Sugianto; Faishal Fachruddin (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
World currency market trading has become one of the many types of work that has been done by the public due to the convenience offered, big profits and the flexibility of time and place in trading. This study aims to predict the movement of EUR / USD currency trends using data mining techniques combined with neural network algorithms compared by linear regression algorithm that can be used as one of the references for traders as an open trading position. Attributes were used in this study namely Open (Opening Price), Close (Closing Price), Highest (Highest Price), Lowest (Lowest Price), for time frame price used is with time frame 1 day and the time period is taken from 3 January 2011 to 15 November 2016. The result of this research is Root Mean Squared Error (RMSE) percentage number as well as additional label prediction result that obtained after validation using sliding windows validation. Best result obtained from testing phase using neural network algorithm which uses 0.006 and 0.003 windowing which results is equal to testing phase that does not use windowing. In other hands, testing phase on linear regression algorithm using windowing resulted in 0.007 and testing phase that does not use windowing that is equal to 0.004. T-test showed that neural network has insignificant result compared with linear regression. T-test result value is 1.00 for testing with windowing and 0.077 for windowless test.